The Relationship of Teachers’ Perception towards Leadership Capacity with Their Demographic Factors at Mon National Middle Schools, in Ye Township, Mon State, Myanmar - Mar, Tin Tin; Ye, Yan (Scholar: Human Sciences, 2016)
The main purpose of this study was to determine the relationships of teachers’ perception towards leadership capacity and their demographic factors: age, education background, work experience, and training experience at Mon National Schools, Ye Township, Mon State, Myanmar. A total of 90 teachers from eight Mon National Middle Schools in the same state and the same township were surveyed for this study. The main source of the data was questionnaires that investigated teachers’ demographic factors including age, education background, work experience, and training experience, and leadership capacities. The collected data were analyzed by using the Descriptive Statistics, Frequency, Percentage, Standard Deviation, Mean, and Pearson Product Moment Correlation. The study found that teachers’ leadership capacities from eight middle schools were perceived as “good enough” in their schools. On the other hand, the correlation analysis found that there were no relationships between teachers’ perceived leadership capacities and teachers’ demographic factors including age, education background, and training experience. However, there was a positive relationship between leadership capacities and teachers’ work experience at Mon National Middle School, Mon State, Myanmar. In order for the schools to become more sustainable, administrators from 8 Mon National Middle Schools are recommended to innovate, develop, and create more opportunities for all teachers to share ideas, to control teacher stability and other uncompleted situations. It could be a valuable research other researcher can conduct the similar research in other organizations and countries, and can also conduct the research on the relationship between leadership capacity and sustained high level of student achievement.